Do Banks Price Environmental Transition Risks? : Evidence from a Quasi-Natural Experiment in a Chinese Province - Huang, Bihong (IMF Working Papers; Working Paper ;, 2021)
This paper assesses the financial risks arising from transition toward a low-emission economy. The environmental DSGE model shows tightening environmental regulation impairs firms' balance sheets, and consequently threatens financial stability in the short term. The empirical analysis indicates that following the implmentation of Clean Air Action Plan, the default rates of high-polluting firms in a Chinese province rose by around 80 percent. Joint equity commercial banks with higher level of independence were able to appropriately price in their exposure to transition risks, while the Big Five commercial banks failed to factor in such risks.